EPENTHESIS IN ELEMENTARY SCHOOL - Meiyanti Nurchaerani; Alfian Alfian; Syahiid H. R. Hartadhi (Journey: Journal of English Language and Pedagogy, 2023)
Focus of this research was regarding epenthesis in written wordsof students in Pasir luhur elementary school, Bandung. the writer assumed to identify [1] the way of epenthesis that is written by students and [2] which grapheme that will be found frequently addthe written words. The researcher used descriptive qualitative research methods in this study, which meant that participants were involved in case studies that produced narratives and descriptive explanations about settings or practices. The object of exploration that the writer analyzed in this study is the handwriting made by 10 representative students in one classroom. From the analysis, the writer found a way that made the result of written word became so identic. The results of the research showed that the students experienced epenthesis by added certain letter in the middle of word. The most frequently epenthesis happened is in consonant grapheme. this research can add to the literature for other researchers in the field of psycholinguistics and become a reference for other researcher for linguistic studies